The importance of the coating material type and amount in the preparation of liquisolid systems based on magnesium aluminometasilicate carrier - Vraníková, Barbora; Svačinová, Petra; Marushka, Julia; Brokešová, Jana; Holas, Ondrej; Tebbens, Jurjen Duintjer; Šklubalová, Zdenka (European journal of pharmaceutical sciences, 2021)
Albeit the preparation of liquisolid systems represents an innovative approach to enhance the dissolution of poorly soluble drugs, their broader utilization is still limited mainly due to the problematic conversion of the liquid into freely flowing and readily compressible powder. Accordingly, the presented study aims to determine the optimal carrier/coating material ratio (R value) for formulations based on magnesium aluminometasilicate (NUS2) loaded with polyethylene glycol 400. Four commercially available colloidal silica were used as coating materials in nine different R values (range of 5 - 100). The obtained results suggested that the higher R value leads to the superior properties of powder mixtures, such as better flowability, as well as compacts with higher tensile strength and lower friability. Moreover, it was observed that the type of coating material impacts the properties of liquisolid systems due to the different arrangement of particles in the liquisolid mixture. To confirm the noted dependency of R value and coating material type, the one- and two-way ANOVA, linear regression and principal component analysis (PCA) techniques were performed. In addition, a comparison of results with the properties of loaded NUS2 itself revealed that LSS with sufficient properties may be prepared even without the coating material.
Keywords: Tablets; tablety; hořčík; Mesoporous silica; oxid křemičitý; prášky, zásypy, pudry; Solubility; Colloidal silica; Liquisolid systems; Neusilin® US2; Silicon Dioxide; příprava léků; Drug Compounding; Carrier/coating material ratio; rozpustnost; Magnesium; Powders